Solar PV Lighting and Studying after Sunset: Analysis of Micro-benefits in Off-grid Rural Ghana - G.Y. Obeng (International Journal of Renewable Energy Development, 2013)
Solar PV light provides school children living in off-grid rural communities theopportunity to have clean and bright lighting to study after sunset. On the contrary, lightingprovided from poor sources can pollute and adversely affect human eyes during reading andwriting. Using indicator-based questionnaires in cross-sectional surveys, households with andwithout solar PV lighting were surveyed in off-grid rural communities in Ghana. The studyinvestigated lighting and children’s studies after sunset. The results indicated that whereassolar PV light of 5-20 watts dc lamps was sufficient for 5-6 children to study together, lightingfrom kerosene lantern could be sufficient for 1-3 children. All things being equal, the resultsshowed that children who use solar PV light to study upto 2 hours after sunset are likely toimprove on their examination results. The extent to which solar PV lighting significantlyimpacts on studying after sunset was established using some identified indicators. Knowledgeof the results provides understanding of the relative constraints in lighting services faced bychildren in rural communities without access to quality lighting. Such micro-level data willhelp to enhance policy and planning efforts to increase access to clean and renewable energybasedlighting devices to achieve efficient visual comfort in off-grid rural communities.